(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
On the basis of 3,5-disubstituted dihydrofuran-2(3H)-ones, hydrazides of substituted γ-hydroxybutyric acids were synthesized, which were further converted into the corresponding thiosemicarbazides and 1,2,4-triazoles. The synthesized compounds have not been previously described in the literature, and they cannot be obtained by any other way.